Stability Switches and Hopf Bifurcation in a Kaleckian Model of Business Cycle - Luca Vincenzo Ballestra; Luca Guerrini; Graziella Pacelli (Abstract and Applied Analysis)
This paper considers a Kaleckian type model of business cycle based on a nonlinear delay differential equation, whose associated characteristic equation is a transcendental equation with delay dependent coefficients. Using the conventional analysis introduced by Beretta and Kuang (2002), we show that the unique equilibrium can be destabilized through a Hopf bifurcation and stability switches may occur. Then some properties of Hopf bifurcation such as direction, stability, and period are determined by the normal form theory and the center manifold theorem.